Optimalisasi Pakan Ikan Mandiri melalui Teknologi Recirculating Aquaculture System (RAS) Berbantuan Solar Cell di Desa Parangargo - Cholily, Yus Mochamad; Effendy, Machmud; Indrawan, Rindya Fery; Subairi, Subairi; Suwandayani, Beti Istanti; Hakim, Riza Rahman (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Waste management issues in Serang Regency, particularly in Desa Cerukcuk, have become a major concern due to the increasing volume of waste that polluting rivers, roadsides, and residential areas. To date, Serang Regency does not have land or facilities for a permanently operating Final Waste Disposal Site (TPSA). This situation has significant environmental impacts and indicates a gap between infrastructure needs and policy implementation practical reality. This study aims to evaluate the commitment of the Serang Regency This community service program focuses on optimizing independent fish feed production through the implementation of a Recirculating Aquaculture System (RAS) combined with a mini Solar Power Plant (PLTS) in Parangargo Village, Wagir District, Malang Regency. The program was designed to address the challenges of high commercial feed costs and dependence on grid electricity that have burdened local fish‐farming groups. The activities included socialization, training in independent fish feed production, installation of the RAS and mini PLTS technologies, business management mentoring, and outcome evaluation. The results show that energy efficiency increased by 20–30% after the installation of the mini PLTS, while feed costs decreased by 10–15% due to the availability of self-produced fish feed. The RAS technology also improved water quality and reduced fish mortality, leading to approximately a 10% increase in production per cycle. Moreover, the managerial and digital marketing skills of the partner groups—“Minaargo” Fish Farming Group and “Matoon” Youth Organization—significantly improved. This program strengthens the village’s food and energy independence and supports the achievement of the university’s Key Performance Indicators.